Novel morphological and genetic features of fumarate hydratase deficient renal cell carcinoma in HLRCC syndrome patients with a tailored therapeutic approach. Issue 11 (7th July 2020) - Wyvekens, Nicolas; Valtcheva, Nadejda; Mischo, Axel; Helmchen, Birgit; Hermanns, Thomas; Choschzick, Matthias; Hötker, Andreas M.; Rauch, Anita; Mühleisen, Beda; Akhoundova, Dilara; Weber, Achim; Moch, Holger; et al.
Abstract: The hereditary leiomyomatosis and renal cell carcinoma syndrome (HLRCC) is defined by germline mutations in the fumarate hydratase ( FH ) gene and associated with leiomyomas and aggressive renal cell carcinomas with FH deficiency. Here, we comprehensively characterize two new patients with HLRCC syndrome on a morphological, immunohistochemical and genetic level. The patients developed aggressive HLRCC syndrome‐associated RCCs, uterine leiomyomas and dermal leiomyomas. One HLRCC syndrome‐associated RCC exhibited an unusual morphology with accumulation of "colloid‐like" cytoplasmic inclusions, which might serve as a novel sentinel feature to trigger further testing. This case showed partially retained FH expression, initially hampering correct diagnosis. Comprehensive next‐generation sequencing analyses of HLRCC syndrome‐associated RCC and leiomyomas in our patients revealed divergent genetic changes in the FH gene in different tumors from the same patient. While all leiomyomas (uterine and cutaneous) showed a FH loss of heterozygosity (LOH) as a wildtype allele inactivating event, one HLRCC‐RCC showed a second, undescribed NM_000143.3; c.947C>T; p.Ala316Val FH mutation accompanying the preexisting splice site mutation c.378+2T>C. In the other HLRCC syndrome‐associated RCC, the FH mutation (NM_000143.3; c.462T>G; p.Asn154Lys with a somatic LOH) represents another variant of unknown significance that we link to HLRCC ‐ and thus classify as likely pathogenic. Due to the specific diagnosis of metastatic HLRCC syndrome‐associated RCC, both cases were treated in first line with bevacizumab/erlotinib and showed remarkable and long lasting responses. These findings allow new morphological and molecular insights into the biology of the HLRCC syndrome, corroborate the "second hit" hypothesis of tumor formation in HLRCC patients and may promote a distinct therapeutic approach.